2016
DOI: 10.2174/1573399812666150930122507
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Uric Acid and Risk for Metabolic Syndrome

Abstract: Our results showed a significant association between hyperuricemia and metabolic syndrome in low-income young adults in Mexico. DR is associated with estimated risk of CVD in type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
4
21
0
4
Order By: Relevance
“…Hyperuricemia causes gouty arthritis (Zamudio-Cuevas et al, 2015 ), kidney stones (Mirheydar et al, 2014 ) and chronic renal failure (Tsai et al, 2017 ), which significantly impact quality of life (Scire et al, 2013 ). Hyperuricemia has also been considered to be a risk factor for metabolic syndrome (Cibicková et al, 2017 ; Rubio-Guerra et al, 2017 ), diabetes mellitus (Wang et al, 2013 ), hypertension (Lyngdoh et al, 2012 ), stroke (Wu et al, 2017 ), chronic kidney disease (Ceriello et al, 2017 ) and cardiovascular disease (Qin et al, 2014 ; Amin et al, 2017 ; Moulin et al, 2017 ). Hyperuricemia is therefore a serious public health problem that should be detected early and treated.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia causes gouty arthritis (Zamudio-Cuevas et al, 2015 ), kidney stones (Mirheydar et al, 2014 ) and chronic renal failure (Tsai et al, 2017 ), which significantly impact quality of life (Scire et al, 2013 ). Hyperuricemia has also been considered to be a risk factor for metabolic syndrome (Cibicková et al, 2017 ; Rubio-Guerra et al, 2017 ), diabetes mellitus (Wang et al, 2013 ), hypertension (Lyngdoh et al, 2012 ), stroke (Wu et al, 2017 ), chronic kidney disease (Ceriello et al, 2017 ) and cardiovascular disease (Qin et al, 2014 ; Amin et al, 2017 ; Moulin et al, 2017 ). Hyperuricemia is therefore a serious public health problem that should be detected early and treated.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences have demonstrated that uric acid induces oxidative damage in a variety of tissues (5,6). Furthermore, hyperuricemia has been identified as an independent risk factor for various chronic conditions such as hypertension, diabetes, cardiovascular disease, metabolic syndrome, and chronic kidney disease (7)(8)(9)(10)(11). It has been recently reported an association between elevated uric acid and a hepatokine that acts as a molecular link between non-alcoholic fatty liver disease and metabolic disorders (12).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from hyperuricemia, several risk factors for development of gout have been postulated in different studies including genetic factors, dietary factors, alcohol consumption, diuretic use, and renal disease [4]. There are studies showing the close association of hyperuricemia or gout with metabolic syndrome [5][6][7]. Gout can be considered as a risk factor for hypertension (HTN), cardiovascular disease, chronic kidney disease (CKD), and diabe-tes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies suggest that uric acid contributes to increased inflammation leading to CKD progression, thus demonstrating the relationship between serum urate levels and kidney function. While hyperuricemia can cause the progression of renal disease, kidney dysfunction itself can increase serum urate levels due to glomerular damage leading to reduced excretion of serum uric acid [6,7].…”
Section: Introductionmentioning
confidence: 99%